Trends in Caesarean Section Rates and Puerperal Purulent–Septic Infections in Kazakhstan: A Five-Year Retrospective Study (2020–2024) (Bangladesh Journal of Medical Science, 2026)
Background The postpartum period involves extensive physiological adjustments, but remains a vulnerable stage for maternal morbidity, particularly from infections. Despite antibiotic prophylaxis, puerperal purulent–septic infections (PSI) persist as clinically significant complications, especially following cesarean section (CS), the most common major obstetric surgery worldwide. Understanding trends in CS and PSI is essential for improving maternal outcomes. Aim To evaluate trends in deliveries, CS rates, and the incidence, clinical characteristics, and complications of PSI in a tertiary maternity hospital in Kazakhstan from 2020 to 2024. Methods A retrospective observational study included 36,317 deliveries over five years. Data on delivery mode, CS type (elective vs. emergency), PSI incidence and type, re-hospitalisation, and associated obstetric complications were extracted from electronic medical records. Descriptive statistics and trend analysis were performed. Results CS rates increased from 23.6% in 2020 to 27.2% in 2024, with emergency procedures predominating. PSI incidence remained low overall but rose from 0.01% in 2022 to 0.20% in 2023–2024. Endometritis was the most frequent infection, followed by wound dehiscence, which increased notably in the final two years. No postpartum sepsis occurred. PSI cases were more common in young, primiparous women and those undergoing emergency CS. Frequent associated conditions included labour abnormalities, fetal hypoxia, chorioamnionitis, obstetric trauma, and premature rupture of membranes. Conclusion Although overall PSI incidence was low, the rising CS rate and wound-related complications underscore the need for strengthened perioperative prevention strategies, targeted risk assessment, and vigilant postoperative monitoring to optimize postpartum outcomes in Kazakhstan.BJMS, Vol. 25 No. 02 April’26 Page: 595-601